Staphylococcus aureus virulence factors and their role in biofilm-associated infections - Božić, Dragana (Archives of Pharmacy, 2024)
Although Staphylococcus aureus colonises the skin and mucous membranes in approximately 30% of healthy individuals, it is also an important pathogen, primarily due to its arsenal of virulence factors that contribute significantly to its ability to cause a variety of infections. These factors include surface proteins that promote adhesion to host tissues, as well as enzymes and toxins that damage host cells and tissue. Important virulence factors such as protein A, which binds to antibodies and evades recognition by the immune system, and various exotoxins such as alpha-toxin and Panton-Valentine leukocidin, which cause cell lysis and tissue destruction, play a crucial role in pathogenesis. The ability of S. aureus to form biofilms on medical devices further increases its persistence and resistance to therapy. Biofilms are structured communities of bacterial cells that are enclosed in a self-produced polymeric matrix and that adhere to biotic or abiotic surfaces. Biofilm-related infections caused by S. aureus, such as infections of medical devices (catheters, prosthetic joints, heart valves, intravascular catheters) and human tissue (chronic rhinosinusitis, chronic wounds, endocarditis and osteomyelitis), are a significant concern in medical settings. Understanding these virulence mechanisms is crucial for the development of targeted therapies and preventive measures to effectively combat S. aureus infections.
Keywords: Staphylococcus aureus; virulence factors; biofilm; biofilm-associated infections